Strain Rate Behaviour of Three Rocks in Tension - CADONI, E.; ANTONIETTI, S.; DOTTA, M.; FORNI, D. (Engineering Transactions, 2014)
The paper presents the dynamic characterization in tension of three rocks under medium and high strain-rates. The tests have been carried out by means of the JRC-Split Hopkinson Tension Bar and an Hydro-Pneumatic Machine, installed in the DynaMat Laboratory of the University of Applied Sciences of Southern Switzerland. The dynamic direct tension tests have been performed at 3 different strain rates (0.1, 10, 100 strain/second) on an orthogneiss, for loading directions 0◦, 45◦ and 90◦ respect to the schistosity, and two different types of marble. Results of the tests show a significantly strain-rate sensitive behaviour, exhibiting dynamic tensile strength increasing with strain-rate. In order to describe the strain rate behaviour of these rocks, the dynamic increase factors in function of the strain rates for tensile strength have been used.